Developing digital capacity of Vietnamese civil servants - Khanh, Tran Thi Bao (International Journal of Innovative Research and Scientific Studies, 2025)
The development of a digital society is a trend in every country, posing many new requirements on digital capacity for state agencies, civil servants, and citizens so that people’s transactions with the state are carried out in the digital environment, and civil servants play the role of the subject in performing this task. This means civil servants must have digital knowledge and skills, form digital capacity to perform public duties, interact, and solve people’s work in the digital environment. This study builds a theoretical framework on the digital capacity of civil servants, including (1) Competency in using digital technology, (2) Competency in exploiting digital data, (3) Competency in performing digital transactions. The author designs a theoretical model aimed at assessing the impact of these three digital capacities on the work results of civil servants in the digital environment. The survey was conducted with a sample size of N = 450 commune-level local civil servants from three provinces with difficult conditions and low growth in three regions of Vietnam, including Lai Chau province (North), Quang Ngai province (Central), and An Giang province (South). The research results show that commune-level local civil servants self-assess their digital capacity at a low level in all three of the above contents. This reality poses requirements for the development and implementation of training and fostering policies on digital capacity for local civil servants in Vietnam today. With that research conclusion, the author suggests some contents to improve policies to develop digital capacity and enhance the quality of local civil servants in Vietnam in the trend of a digital society.